Mediaeval and modern metaphorical concepts of emotions - Štrmelj, Lidija (ELOPE (Ljubljana), 2014)
This article aims to study emotion metaphors found in a selection of Chaucer's Canterbury Tales and compare them with conventional modern metaphors from current dictionaries and other sources, in order to find out whether mediaeval emotional metaphorical concepts have survived to the present day and, if so, what changes can be perceived in them. The study is based on the cognitive theory of metaphor, as developed by George Lakoff and Mark Johnson (1980) in Metaphors We Live By.
Keywords: čustvene metafore; emotivne metafore; kognitivna teorija metafor; konvencionalne metafore; metaforični koncepti; sodobne metafore; srednjeveške metafore